Pd ultra-small clusters as precursors for silica-encapsulated Pd nanoreactors: highly sinter-resistant catalysts - Samanta, Anupam; Devi, R. Nandini (Chemcatchem, 2013)
Sintering and consequent deactivation in supported metal catalysts is a severe problem encountered in heterogeneous catalysis. This problem can be addressed by encapsulating active metal nanoparticles within inert oxides such as silica, provided the oxide shell is porous to enable access of reactant molecules to the nanoparticle surface to facilitate catalysis. We report the synthesis of highly sinter-resistant silica-encapsulated Pd catalysts with nanoparticle sizes stabilized at (3.4 +/- 0.6)nm at high temperatures of approximately 750 degrees C. The synthesis was achieved by utilizing thiol-protected ultra-small clusters of Pd as precursors for silica encapsulation. The ultra-small clusters were synthesized by using propyl ammonium functionalised thiols making them water-dispersible and amenable for silica encapsulation. Abundance of organics also aided in creating porosity subsequent to calcination at high temperatures.
Keywords: cluster compounds; Encapsulation; nanoreactors; Palladium; silicates

Photocatalytic hydrogen generation and CO2 conversion using g-C3N4 decorated dendritic fibrous nanosilica: role of interfaces between silica and g-C3N4 - Rawool, Sushma A.; Samanta, Anupam; Ajithkumar, T. G.; Kar, Yusuf; Polshettiwar, Vivek (ACS Applied Energy Materials, 2020)
We have synthesized g-C3N4 decorated over dendritic fibrous nanosilica (DFNS). The generation of C-N-Si interfaces by coating each fiber of DFNS with g-C3N4 not only provided high surface area but also affected the optical and electronic properties of the composite. The catalyst synthesis reproducibility issue of g-C3N4 was resolved using a vacuum-sealed quartz tube. The extended light absorption in the visible region, enhanced lifetime of photogenerated charge carriers due to the formation of interfaces between silica and g-C3N4 (confirmed by solid-state NMR), and increased surface area result in the improved photocatalytic activity of DFNS/g-C(3)N(4)for hydrogen generation and CO2 conversion.
Keywords: CO2 conversion; DFNS; g-C3N4; Hydrogen generation; nanocatalysts; photocatalysts; Solid-state NMR